2015
DOI: 10.1038/tp.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of rapid eye movement sleep in humans

Abstract: The trait-like nature of electroencephalogram (EEG) is well established. Furthermore, EEG of wake and non-rapid eye movement (non-REM) sleep has been shown to be highly heritable. However, the genetic effects on REM sleep EEG microstructure are as yet unknown. REM sleep is of special interest since animal and human data suggest a connection between REM sleep abnormalities and the pathophysiology of psychiatric and neurological diseases. Here we report the results of a study in monozygotic (MZ) and dizygotic (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…These serve as markers for typical sleep, and as clinically relevant indicators of differentiated electroencephalograms in schizophrenia (Boutros, Mucci, Vignapiano, & Galderisi, ; Manoach et al., ). Twin studies have reported a strong genetic component in both REM (Adamczyk et al., ) and NREM sleep (Ambrosius et al., ), as well as spindle activity, with some reports suggesting a hereditability up to 96% in the 8–16 Hz sleep EEG range (De Gennaro et al., ). In addition to genetics, certain developmental and environmental factors also play a part in determining sleep EEG patterns.…”
Section: Discussionmentioning
confidence: 99%
“…These serve as markers for typical sleep, and as clinically relevant indicators of differentiated electroencephalograms in schizophrenia (Boutros, Mucci, Vignapiano, & Galderisi, ; Manoach et al., ). Twin studies have reported a strong genetic component in both REM (Adamczyk et al., ) and NREM sleep (Ambrosius et al., ), as well as spindle activity, with some reports suggesting a hereditability up to 96% in the 8–16 Hz sleep EEG range (De Gennaro et al., ). In addition to genetics, certain developmental and environmental factors also play a part in determining sleep EEG patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, measures which themselves reflect the functioning of complex neural systems might be exceptions as they capture the end product of complicated genetic pathways involving complementary and possible substitutable mechanisms. The sleep EEG is a good candidate for such a measure, given its high individual stability 24 , 27 , 85 , strong genetic determination 27 , 32 , 86 and the fact that it reflects the events in large, functionally connected neural assemblies free from contamination by wakeful mentation and movement artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the high reliability of the sleep EEG spectrogram was demonstrated well outside the sigma range in NREM 25 29 . Notably, the descriptive parameters 30 , 31 as well as EEG characteristics 32 , 33 of REM sleep are similarly stable and heritable. Therefore, the scarcity of data on the relationship between IQ and sleep EEG features other than sleep spindles is somewhat surprising.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, greater similarity between monozygotic twins as compared to dizygotic twins can be attributed to the larger proportion of shared genes. Studies in adult twins have shown that the sleep EEG power spectrum is highly heritable 13 , 36 38 .…”
Section: Introductionmentioning
confidence: 99%